2010
DOI: 10.1097/bpo.0b013e3181d8fa53
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Passive Stiffness of 2 Constructs of Varus Proximal Femoral Osteotomy: External Fixator or Blade Plate

Abstract: The results support the hypothesis that external fixation is a biomechanically sound alternative to internal fixation of varus intertrochanteric osteotomies, in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Paliobeis et al [18] assessed the mechanical properties of an EF and a BP for fixation of proximal femoral osteotomies and concluded that EF is a biomechanically sound alternative to internal fixation. In our study, there were no position changes of the fragments, no nonunions, and no device failures even in some obese patients, suggesting that the MAC EF system provides efficient mechanical strength and stability (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Paliobeis et al [18] assessed the mechanical properties of an EF and a BP for fixation of proximal femoral osteotomies and concluded that EF is a biomechanically sound alternative to internal fixation. In our study, there were no position changes of the fragments, no nonunions, and no device failures even in some obese patients, suggesting that the MAC EF system provides efficient mechanical strength and stability (Fig.…”
Section: Discussionmentioning
confidence: 99%